SUPPLEMENTATION OF IRON SUCROSE IN SEVERE ANAEMIC GOATS - Annarao; Vivek R Kasaralikar; D. Dilip Kumar; B.G. Ravindra; Shrikant Kulkarni; S.C. Halmandage (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Parasitic infestation is the primary aetiology of anaemia in goats. Chronic parasitic infestation being the most common cause for severe anaemia in addition to the elimination of aetiology, supportive therapy is necessary for the early regain of normal physiological and haemato-biochemical parameters. The present study was conducted at the Veterinary clinical complex, Veterinary College, Bidar. Six severely anaemic goats were selected for the present study to know the efficacy of iron sucrose as supportive therapy. Rectal temperature, heart rate and respiratory rate were recorded as per the standard procedures. Haemato-biochemical parameters were estimated on day 0 and day 15 of post therapy as per the standard procedures. Goats were promptly treated for the primary complaint, dipped, and dewormed to eliminate the Endecto parasites. Selected goats were supplemented with 50 mg of iron sucrose on every alternate day four times in 100 mL normal saline solution by slow intravenous route. A significant (p< 0.05) improvement was observed in physiological and haemato-biochemical parameters after 15 days of post therapy.